EKSPERIMENTASI MODEL PEMBELAJARAN PROBLEM BASED LEARNING (PBL), DISCOVERY LEARNING (DL), DAN COOPERATIVE LEARNING (CL) DITINJAU DARI KECERDASAN INTERPERSONAL SISWA - Berti Okta Sari; Mardiyana Mardiyana; Dewi Retno Sari S (Jurnal Pembelajaran Matematika, 2015)
Abstract: The objectives of this research were to investigate: (1) which learning model of the PBL, DL, and CL models results in a better achievement in mathematics; (2) which students of the students with high, moderate, and low interpersonal intelligences have a better learning achievement in mathematics; (3) in each interpersonal intelligence, which learning model of the PBL, DL, and CL models results in a better achievement in mathematics; and (4) in each learning model, which students of the students with high, moderate, and low interpersonal intelligences have a better learning achievement in mathematics. This research used the quasi experimental research method with the factorial design of 3 x 3. Its population was all of the students in Grade VIII of State Junior Secondary Schools of Bengkulu Selatan Regency, Bengkulu Province in Academic Year 2014/2015. The samples of research were taken by using the stratified cluster random sampling technique. The balance test of research used the one-way analysis of variance with unbalanced cells. The pre-requisite test of ANAVA used Lilliefors’s normality test, Bartlett’s homogeneity test. The proposed hypotheses of research were tested by using the two-way analysis of variance with unbalanced cells. The results of research are as follows: 1) the PBL model results in a better learning achievement in mathematics than the DL and CL models, and the DL model results in a better learning achievement in mathematics than the CL model; 2) the students with the high interpersonal intelligence have a better learning achievement in mathematics than those with the moderate and low interpersonal intelligences, and the students with the moderate interpersonal intelligence have a better learning achievement in Mathematics than those with the low interpersonal intelligence; 3) in each interpersonal intelligence level, the PBL model results in a better learning achievement in mathematics than the DL and CL models, and the DL model results in a better learning achievement in mathematics than the CL model; 4) in each learning model, the students with the high interpersonal intelligence have a better learning achievement in mathematics than those with the moderate and low interpersonal intelligences, and the students with the moderate interpersonal intelligence have a better learning achievement in mathematics than those with the low interpersonal intelligence.Keywords:  Problem-based learning, discovery learning, cooperative learning, interpersonal intelligence, learning achievement in Mathematics